Ugonin M, a Helminthostachys zeylanica Constituent, Prevents LPS-Induced Acute Lung Injury through TLR4-Mediated MAPK and NF-κB Signaling Pathways - Kun-Chang Wu (Molecules, 2017)
Helminthostachys zeylanica (L.) Hook. is plant that has been used in traditional Chinese medicine for centuries for the treatment of inflammation, fever, pneumonia, and various disorders. The aims of the present study are to figure out the possible effectiveness of the component Ugonin M, a unique flavonoid isolated from H. zeylanica, and to elucidate the mechanism(s) by which it works in the LPS-induced ALI model. In this study, Ugonin M not only inhibited the production of pro-inflammatory mediators such as NO, TNF-α, IL-1β, and IL-6, as well as infiltrated cellular counts and protein content in the bronchoalveolar lavage fluid (BALF) of lipopolysaccharides (LPS)-induced acute lung injury (ALI) mice, but also ameliorated the severity of pulmonary edemas through the score of a histological examination and the ratio of wet to dry weight of lung. Moreover, Ugonin M was observed to significantly suppress LPS-stimulated protein levels of iNOS and COX-2. In addition, we found that Ugonin M not only obviously suppressed NF-κB and MAPK activation via the degradation of NF-κB and IκB-α as well as ERK and p38MAPK active phosphorylation but also inhibited the protein expression level of TLR4. Further, Ugonin M treatment also suppressed the protein levels of MPO and enhanced the protein expressions of HO-1 and antioxidant enzymes (SOD, GPx, and CAT) in lung tissue of LPS-induced ALI mice. It is anticipated that through our findings, there is strong evidence that Ugonin M may exert a potential effect against LPS-induced ALI mice. Hence, Ugonin M could be one of the major effective components of H. zeylanica in the treatment of inflammatory disorders.